2022
DOI: 10.1039/d1dt04102a
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on catalytic nitrite reduction reaction by bioinspired CuII complexes

Abstract: Catalytic nitrite reductions by CuII complexes containing anionic Me2Tp, neutral Me2Tpm, or neutral iPrTIC ligands in the presence of L-ascorbic acid, which served as an electron donor and proton source,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In contrast, a reaction of the nonheme-Fe II (dinitrite) complex with RSH affording disulfide (RSSR) and NO has been shown to proceed through an initial protonation of the nitrite moiety . Although the transformation of NO 2 – to NO at various redox-active transition metals such as Fe/Co/Ni/Cu has been relatively well explored in the presence of a diverse array of exogenous reductants (e.g., phosphine, CO, VCl 3 , thiol, phenol, and ene-diols), the examples of analogous reactions at a redox-inactive [Zn II ] site and the underlying factors for promoting the reaction remain poorly understood. Notably, the NO-releasing reactions of [Zn II ]–nitrite complexes in the presence of external reductants like benzylthiol and 3,5-di- tert -butylcatechol have been reported to be slow. , Herein, this report investigates the thiol reactivity of a previously reported CA-model bound to nitrite, namely [( Bn 3 Tren )­Zn II (κ 2 - O : O′ -nitrite)]­(ClO 4 ) ( 1 ) (Figure ), aiming to disclose biologically relevant conditions for an efficient transformation of nitrite-to-NO at a zinc­(II) site.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a reaction of the nonheme-Fe II (dinitrite) complex with RSH affording disulfide (RSSR) and NO has been shown to proceed through an initial protonation of the nitrite moiety . Although the transformation of NO 2 – to NO at various redox-active transition metals such as Fe/Co/Ni/Cu has been relatively well explored in the presence of a diverse array of exogenous reductants (e.g., phosphine, CO, VCl 3 , thiol, phenol, and ene-diols), the examples of analogous reactions at a redox-inactive [Zn II ] site and the underlying factors for promoting the reaction remain poorly understood. Notably, the NO-releasing reactions of [Zn II ]–nitrite complexes in the presence of external reductants like benzylthiol and 3,5-di- tert -butylcatechol have been reported to be slow. , Herein, this report investigates the thiol reactivity of a previously reported CA-model bound to nitrite, namely [( Bn 3 Tren )­Zn II (κ 2 - O : O′ -nitrite)]­(ClO 4 ) ( 1 ) (Figure ), aiming to disclose biologically relevant conditions for an efficient transformation of nitrite-to-NO at a zinc­(II) site.…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of various Cu-(I) 20−30 and Cu(II) 22,26−29,31−41 model compounds with nitrite was investigated, and several Cu(II)−NO 27,42−44 and Cu(I)−NO 45−47 studies by Fujii and co-workers showed that a stepwise protonation mechanism is operative in dichloromethane, 23,25 and work by Hsu and co-workers sheds light on the possible formation of HNO 2 at low pH. 38 In recent years, bio-inspired CuNiRs are also studied using electrochemical methods in both organic 34,48,49 and aqueous solutions. 11−14,37,50−52 The first electrochemical studies on nitrite reduction were reported in 1993 and 1995 by the group of Komeda.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The one-electron reduction of NO 2 – to NO is the second step of the denitrification process and occurs in the metalloenzyme nitrite reductase (NiR), containing either iron or copper in its active site. , In CuNiRs, reduction of NO 2 – takes place at a mononuclear type 2 Cu site (Figure a). , Inspired by the enzymatic process, nitrite reduction is studied using bio-inspired CuNiRs. The reactivity of various Cu­(I) and Cu­(II) , , model compounds with nitrite was investigated, and several Cu­(II)–NO , and Cu­(I)–NO complexes were characterized. In addition, studies by Fujii and co-workers showed that a stepwise protonation mechanism is operative in dichloromethane, , and work by Hsu and co-workers sheds light on the possible formation of HNO 2 at low pH …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on the reduction of NO 2 – by Cu complexes have been reported. Spectroscopic studies and X-ray crystal structure determinations have revealed important aspects of NO 2 – reduction at Cu active centers. Woollard-Shore et al reported the synthesis, characterization, and catalytic properties of four Cu­(II) complexes as catalytic agents for NO 2 – reduction . Their crystallographic study revealed three different coordination modes: η 1 -NO 2 , η 1 -ONO, and η 2 -ONO.…”
Section: Introductionmentioning
confidence: 99%